Ninety days of repeated gavage administration of Rhodiola imbricata extract in rats. Issue 5 (21st September 2011) - Tulsawani, Rajkumar; Meena, Dharmendra Kumar; Shukla, Hem; Sharma, Priyanka; Meena, Ram Niwas; Gupta, Vanita; Kumar, Ratan; Divekar, Harish Madan; Sawhney, Ramesh Chand
ABSTRACT: Rhodiola imbricata is a high‐altitude plant, possesses adaptogenic, immunomodulatory, anti‐oxidant and cytoprotective activity, and is widely used in traditional medicine. The present study was designed to ascertain the safety of aqueous extract of R . imbricata root when administered by gavage to rats for 90 days. Four groups of animals, each consisting of 15 males and 15 females, were administered 0, 100, 250 or 500 mg kg −1 extract, in a single dose per day. The experimental rats when administered 100 mg kg −1 of extract did not show any significant change in their body weight gain, organ/body weight ratio, or histological, hematological and biochemical variables studied. However, at higher doses of 250 and 500 mg kg −1 extract, an increase in the body weight of rats of both the sexes was apparent without any change in their organ/body weight ratio. Furthermore, a noteworthy increase in plasma glucose and protein levels was recorded at both the higher doses, which were restored to normal after a 2‐week withdrawal of treatment. Based on the findings of this study, the no observed effect level was 100 mg kg −1 body weight per day of aqueous root extract of R . imbricata in rats administered subchronically. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : The present study was carried out to assess the safety of aqueous root extract of Rhodiola imbricata after its sub chronic (90 days) administration in rats. The extract was found potentially non‐toxic when administered sub‐chronically. Based on the findings, 100 mg/kg dose of extract was observed to be No Observed Effect Level (NOEL) and its five times higher dose was considered the No Observed Adverse Effect Level (NOAEL) for aqueous root extract of Rhodiola imbricata in rats.